Innovative financing for renewable energy project development – recent case studies in North America. Issue 1 (2nd January 2018) - Miller, Lindsay; Carriveau, Rupp; Harper, Scott
Abstract: Renewable energy can address increasing energy demand while mitigating the effects of climate change. High capital costs and long payback periods require most projects to secure financing for a portion of the initial costs. Market-based incentives and policies can be credited with lowering development costs, but these come with uncertainties and expiration dates. To secure financing, project developers have turned to innovative mechanisms. This paper presents case studies of innovative financing for renewable energy development in North America. Examples include financing through public capital vehicles, hybrid and carbon bonds, and through corporate power purchase agreements. The objective is to determine which mechanisms or which components of these financing packages are replicable for the purpose of encouraging developers to seek the most advantageous solutions.